Visual didactic regulators as instruments of learning activity: Development and applied aspects - V. E. Steinberg; N. N. Manko; L. V. Vakhidova; D. R. Fatkhulova (Образование и наука)
Introduction. The competitive advantage in the field of critical knowledge and technology exacerbates the problem of the effectiveness of intellectual activity and the means of its support in science, production and education. Such visual aids, formed by conceptual and graphic elements, such as concept maps, frames, structural logic diagrams, etc., contribute to the theoretical analysis and generalisation of the formed images and representations of learners. According to the degree of the development of these visual aids, the emphasis shifts from the function of visibility to the function of the organisation of activities. The term “visibility” (associated with the initial images of perception and representation) is substituted by the term “regulator” (focused on the organisation of further activities of the student). The hypothesis assumes the expediency of the development of conceptual and graphic means of visualisation in the form of visual didactic regulations, which are the subject of research.The present research aims: to discuss the problem of the creation of didactic regulations for educational activities; to study the development of conceptual-graphic means of visibility and factors for improving their functionality; to forecast the development of this type of means based on the visualisation of the logical-semantic modelling of knowledge; to clarify terminology and applied aspects; and to conduct experimental approbation in the conditions of distance learning.Methodology and research methods. The research methodology is based on the fundamental didactic principle of visualisation, which is necessary for the transition in the process of cognition from sensory perception to abstract thinking and contributes to the combination of abstract thinking with visualisation in teaching. The research methodology is also based on the method of logical-semantic modelling of knowledge and the following criteria for the study of conceptual-graphic means of visualisation: the application of the cognitive principles of knowledge representation; the use of universal instructional analysis activities to transform knowledge; the applicability of graphical representation of content. The methodology for the formation of didactic regulations included a visual presentation of the results of logical-semantic modelling of knowledge using universal educational actions and coordinate-matrix graphics. The method of experimental approbation of regulations in distance learning involved: the participation of students of four specialities and university teachers; a questionnaire survey of students; mastering, designing and using didactic regulations on the topic of experimental studies.Results and scientific novelty. The search on the databases of scientific documents of the Russian Academy of Education, the Electronic Scientific Library, Scopus, WOS and the Internet revealed the apparent lack of research and development of didactic regulations of a conceptual-graphic type. It was established that the main reason for the development of conceptual and graphic means of visualisation is the complexity of the tasks to be solved in science, production and education. It is demonstrated that the improvement of the functionality of conceptual and graphical tools is explained by the application of the principles of cognitive visual representation of knowledge and the method of logical-semantic modelling. The basic structures of the regulations were predicted and formed; the terminology of the research approach was clarified; the application of the tools for educational and project-based activities, interfaces of computer training programs is considered.Practical significance. The functionality of visual didactic regulators expands the potential of visibility and complements the tools of the teacher and the student. Moreover, they can be used in teaching technologies, research activities and design, when creating computer training programs.